PELATIHAN TATA KELOLA PENGEMBANGAN MANAJEMEN MUTU SEKOLAH BAGI KEPALA SEKOLAH - Diding Nurdin; Abu Bakar; Sururi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The training on governance development of school quality management was carried out for 10 principals of public elementary schools (SDN) aimed at assisting school principals in developing the quality of school management based on the 8 National Education Standards. The training is carried out offline with the Health protocol with an andragogic approach. The presenters explore ideas, ideas, and expectations of school principals to be analyzed with SWOT analysis and the practice of reviewing the Education Unit Accreditation Instrument (IASP). The results of the training showed a change in the attitudes, knowledge and skills of school principals in developing SNP-based school quality management.